Studi kelayakan bisnis taktik Pemasaran E-Commerce Untuk Meningkatkan Eksport Komoditi Hasil Perkebunan di masa Pandemic di PT. Gamael Dwicitakarya Bekasi Jawa Barat - Elpy Siti Nurhalimah; H.Patria Supriyoso (PT FORMOSA CENDEKIA GLOBAL, 2022)
In dealing with economic problems during the COVID-19 pandemic, all parties must work together to resolve this global issue. Based on these considerations, the research problem that will be discussed by the author is to anticipate the impact of COVID-19 on the economy in Indonesia by opening business directions, namely by opening up e-commerce opportunities as a substitute for large-scale marketing and export sales of plantation products.